Study on Bacteria Isolates and Antimicrobial Resistance in Wildlife in Sicily, Southern Italy - Delia Gambino; Domenico Vicari; Maria Vitale; Giorgia Schirò; Francesco Mira; Maria La Giglia; Alessandra Riccardi; Antonino Gentile; Susanna Giardina; Anna Carrozzo; Valentina Cumbo; Antonio Lastra; et al. (Microorganisms, 2021)
Wild environments and wildlife can be reservoirs of pathogens and antibiotic resistance. Various studies have reported the presence of zoonotic bacteria, resistant strains, and genetic elements that determine antibiotic resistance in wild animals, especially near urban centers or agricultural and zootechnical activities. The purpose of this study was the analysis, by cultural and molecular methods, of bacteria isolated from wild animals in Sicily, Italy, regarding their susceptibility profile to antibiotics and the presence of antibiotic resistance genes. Bacteriological analyses were conducted on 368 wild animals, leading to the isolation of 222 bacterial strains identified by biochemical tests and 16S rRNA sequencing. The most isolated species was Escherichia coli, followed by Clostridium perfringens and Citrobacter freundii. Antibiograms and the determination of resistance genes showed a reduced spread of bacteria carrying antibiotic resistance among wild animals in Sicily. However, since several wild animals are becoming increasingly close to residential areas, it is important to monitor their health status and to perform microbiological analyses following a One Health approach.